2017
DOI: 10.1136/emermed-2016-206353
|View full text |Cite
|
Sign up to set email alerts
|

Ibuprofen versus placebo effect on acute kidney injury in ultramarathons: a randomised controlled trial

Abstract: BackgroundDespite concerns that non-steroidal anti-inflammatory drugs (NSAIDs) contribute to acute kidney injury (AKI), up to 75% of ultramarathon runners ingest these during competition. The effect of NSAID on AKI incidence in ultramarathon runners is unclear.MethodsMultisite randomised double-blind placebo-controlled trial in the Gobi, Atacama, Ecuador and Sri Lankan deserts to determine whether ibuprofen (400 mg every 4 hours) would be non-inferior to placebo during a 50-mile (80 km) foot race. The primary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
56
1
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(59 citation statements)
references
References 24 publications
1
56
1
1
Order By: Relevance
“…It has been reported that up to 75% of ultra-endurance athletes use NSAIDs during the race (Wharam et al, 2006). Our present results, excluding subjects with the use of NSAIDs demonstrated a high decreased prevalence of AKI compared to studies whose included them (McCullough et al, 2011;Hewing et al, 2015;Mansour et al, 2017), highlighting the deleterious effects on renal function of the use of NSAIDs during an ultramarathon race, able to exacerbate renal injury (Lipman et al, 2017).…”
Section: Discussionsupporting
confidence: 45%
See 3 more Smart Citations
“…It has been reported that up to 75% of ultra-endurance athletes use NSAIDs during the race (Wharam et al, 2006). Our present results, excluding subjects with the use of NSAIDs demonstrated a high decreased prevalence of AKI compared to studies whose included them (McCullough et al, 2011;Hewing et al, 2015;Mansour et al, 2017), highlighting the deleterious effects on renal function of the use of NSAIDs during an ultramarathon race, able to exacerbate renal injury (Lipman et al, 2017).…”
Section: Discussionsupporting
confidence: 45%
“…Further risk factors for acute kidney injury in ultra-endurance runners have been demonstrated as the use of NSAIDs (Lipman et al, 2017) sometimes leading to dramatic clinical situation of acute renal failure needing hospitalization (Poussel et al, 2013). In a previous "Infernal-Trail" race (2014), we observed a prevalence of self-medication during the race at 18% and NSAIDs has been consumed in half of the cases (Didier et al, 2017).…”
Section: Discussionmentioning
confidence: 77%
See 2 more Smart Citations
“…A study of prolonged exercise (marathon) also demonstrated a decline in eGFR and increased biomarkers for kidney injury, but these were not associated with acute exercise [29]. Nonsteroidal anti-inflammatory drugs taken by athletes for analgesic purposes may exacerbate kidney damage, especially related to severe dehydration [30]. Acute exercise could induce significant creatinine elevation and a decrease in eGFR compared with baseline levels in the present study, but these levels gradually recovered after exercise ( Figure 3A,B).…”
Section: Discussioncontrasting
confidence: 38%